2021
DOI: 10.3389/fpsyt.2020.599588
|View full text |Cite
|
Sign up to set email alerts
|

The Antidepressant-Like Effects of a Clinically Relevant Dose of Ketamine Are Accompanied by Biphasic Alterations in Working Memory in the Wistar Kyoto Rat Model of Depression

Abstract: Major depressive disorder (MDD) is the leading cause of disability worldwide. The majority of antidepressant drugs require several weeks or months of treatment to demonstrate efficacy and a subset of patients are resistant to such interventions. Ketamine demonstrates rapid and long-lasting antidepressant effects in treatment resistant patients; however, side effects may limit its widespread clinical utility. The pharmaceutical industry is engaged in developing novel rapid-acting antidepressant drugs and the es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
(82 reference statements)
1
4
0
Order By: Relevance
“…However, additional studies are warranted to explore the antidepressant effects of traxoprodil in different concentrations and durations of treatment. The FST and TST, also known as behavioral despair models, have become the most widely used models for assessing the effects of antidepressants due to strong reliability, high predictive efficacy, and easy operation [31,32]. Consistent with previous literature [33,34], our study showed that immobility time during the FST and TST was prolonged in CUMS mice compared to control mice.…”
Section: Discussionsupporting
confidence: 90%
“…However, additional studies are warranted to explore the antidepressant effects of traxoprodil in different concentrations and durations of treatment. The FST and TST, also known as behavioral despair models, have become the most widely used models for assessing the effects of antidepressants due to strong reliability, high predictive efficacy, and easy operation [31,32]. Consistent with previous literature [33,34], our study showed that immobility time during the FST and TST was prolonged in CUMS mice compared to control mice.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, electroconvulsive stimulation, the equivalent of electroconvulsive treatment in humans, does reduce WKY immobility in the FST without increasing general activity measures [ 245 , 246 ]. Other therapies that reduce anhedonia in stressed WKYs include deep brain stimulation [ 234 , 247 , 248 ] and low doses of ketamine [ 234 , 249 - 251 ], which have shown similar clinical efficacy in treating pharmacoresistant MDD patients [ 252 , 253 ]. We do not know if these treatments in humans generate active coping or reduce passive coping with stress, but we know that they are effective in reducing depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…As a common but severe mental health disorder, PPD poses a serious global burden worldwide. Multiple animal models of PPD have been established to explore its pathogenesis, including stress-induced (Boccia et al, 2007;Haim et al, 2016), HSPinduced (Stoffel and Craft, 2004;Schiller et al, 2013), and transgenic animal models (Tillmann et al, 2019;McDonnell et al, 2020). Among these, the HSP-induced model is commonly used due to its advantages such as good reproducibility and easier procedure.…”
Section: Discussionmentioning
confidence: 99%